Comparative Analysis of MicroRNA Expression among Benign and Malignant Tongue Tissue and Plasma of Patients with Tongue Cancer - Rabinowits, Guilherme; Bowden, Michaela; Flores, Ludmila M.; Verselis, Sigitas; Vergara, Victoria; Jo, Vickie Y.; Chau, Nicole; Lorch, Jochen; Hammerman, Peter S.; Thomas, Tom; Goguen, Laura A.; Annino, Donald; et al. (Frontiers in Oncology, 2017)
Background Identification of a microRNA (miRNA) pattern to be used as a biomarker for HNSCC is challenging given the heterogeneity of the disease and different methodologies used. To better define the field, we performed a prospective analysis of blood, tumor, and paired benign tissues in tongue squamous cell carcinoma (SCC) patients. Methods Plasma samples were collected prior to surgery, and paired tumor and benign tissue blocks were collected from tongue cancer resections. Circulating free and exosomal miRNA, and paired tumor and benign tissues miRNA were analyzed. TaqMan-based miRNA arrays were used to quantitate the expression of 747 human miRNAs. The comparative Ct method assessed the miRNA profile results, and Student’s t-test determined statistical significance between tumor and benign samples. Results Sixteen of 359 miRNAs detected were differentially expressed between paired tumor and benign tissue. Nine were upregulated, and seven downregulated in tumor tissue. All nine upregulated and six of seven downregulated tumor miRNAs were expressed in circulating exosomes. In contrast, eight of nine upregulated and four of seven downregulated tumor miRNAs were circulating free in the plasma. Conclusion An aberrantly expressed pattern of miRNA was identified in both tumor and plasma of patients with tongue SCC, suggesting this may be a biomarker for SCC of the oral tongue. Circulating exosomes appear to be a more reliable method for evaluation of circulating tumor-miRNA expression. Further studies with a larger cohort of patients and serial blood samples are needed to validate our findings.